Expanding Financing for Biodiversity Conservation : Experiences from Latin America and the Caribbean - World Bank (Washington, DC, 2014)
The Latin America and Caribbean Region has been at the forefront of global biodiversity conservation, dedicating 20 percent of its land to protected areas compared to 13 percent in the rest of the developing world. This progress has stretched available budgets for conservation with estimates indicating that a twofold increase would be necessary to achieve optimal management of existing protected areas based on 2008 data. Recognizing the importance of this financing challenge, this document presents examples of how the region is successfully exploring news ways and sources of finance for biodiversity conservation. It is intended as an input to the global discussions on biodiversity financing drawing from a selective review of concrete experiences where governments are tapping nonpublic finance sources in effective partnerships. The cases reviewed point to common features contributing to their success: (i) variety in arrangements; (ii) enabling legal and institutional support; (iii) capacity based on record of experience; (iv) building social capital; (v) clarity about conservation objectives; (vi) strong government leadership in guiding biodiversity conservation policies and programs.